Epigenetic alterations of adenomatous polyposis coli (APC), retinoic acid receptor beta (RARÎ²) and survivin genes in tumor tissues and voided urine of bladder cancer patients - Berrada, N.; Amzazi, S.; Ameziane el hassani, R.; Benbacer, L.; El mzibri, M.; Khyatti, M.; Chafiki, J.; Abbar, M.; Al bouzidi, A; Ameur, A.; Attaleb, M. (Cellular and Molecular Biology, 2012)
he CpG promoter methylation has been reported to occur frequently in bladder cancer. Moreover, analysis of gene methylation has been shown to be feasible from voided urine and can be detected with a high degree of sensitivity. The aim of this present study is to determine how methylation patterns of APC, RARÎ² and Survivin genes change during bladder carcinogenesis and to evaluate whether DNA methylation could be detected in urine sediment. Using the sensitive assay of MSP, we explored the promoter methylation status for the three genes in tumor specimens and urine sediment DNA from 32 bladder cancer patients. Methylation frequencies of the tested genes in tumor specimens were 100%, 75% and 84.4% for APC, RARÎ² and Survivin, respectively. Hypermethylation of APC was found in all pathological grades and stages of bladder cancer. More frequent promoter hypermethylation of RARÎ² and Survivin was observed in high grade tumors and the hypermethylation increased from low to high stages, but there was no significant correlation between stages/grades and hypermethylation of these two gene promoters. In order to investigate clinical usefulness for noninvasive bladder cancer detection, we further analyzed the methylation status in urine samples of bladder cancer patients. Methylation of the tested genes in urine sediment DNA was detected in the majority of cases that were hypermethylated in tumor samples (93.7%) and the frequencies were 79.3% 70.8% and 96.3% for APC, RARÎ² and Survivin, respectively. Our results indicate that methylation of APC, RARÎ² and Survivin gene promoters is a common finding in patients with bladder carcinoma. The ability to detect methylation not only in bladder tissue, but also in urine sediments, suggests that methylation markers are promising tools for noninvasive detection of bladder cancer.